2010
DOI: 10.4314/acsj.v17i4.54303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pathogenic isolates in Ethiopia for the control of chocolate spot in Faba bean

Abstract: Faba bean (Vicia faba L.) is one of the earliest domesticated food legumes in Ethiopia and is now cultivated on large areas in many countries. Production of the crop is, however, constrained by several disease infections including fungal diseases. The objectives of this work was to find out natural prevalence of Bacillus isolates on faba bean leaves in Amhara Regional state of Ethiopia; and to identify potential biocontrol agents for the management of chocolate spot (Botrytis fabae). Thirty eight distinct grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
(10 reference statements)
2
13
0
Order By: Relevance
“…Similar results have been reported by [19]. [20] reported that Bacillus were promising bacterial antagonists for the control of plant diseases, because of their simple nutritional requirements, which allow them to colonize on dry surfaces for long periods of time, the rapid use of many available nutrients and endospores resistant to withstand many environmental risks. Bacillus species, in-cluding B. amyloliquefaciens [21] [22] [23], significantly reduce the severity of plant pathologies on various hosts under greenhouse or field conditions [24].…”
Section: Discussionsupporting
confidence: 87%
“…Similar results have been reported by [19]. [20] reported that Bacillus were promising bacterial antagonists for the control of plant diseases, because of their simple nutritional requirements, which allow them to colonize on dry surfaces for long periods of time, the rapid use of many available nutrients and endospores resistant to withstand many environmental risks. Bacillus species, in-cluding B. amyloliquefaciens [21] [22] [23], significantly reduce the severity of plant pathologies on various hosts under greenhouse or field conditions [24].…”
Section: Discussionsupporting
confidence: 87%
“…Faba bean is a valuable protein-rich food that provides a large sector of the human populations in developing countries with a cheap protein source thus partly compensating for the large deficiency in animal protein sources. It is one of the earliest domesticated food legumes and is now cultivated on large areas in many countries due to its high nutritive value in terms of energy and protein contents (24-30%) (Sahile et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus spp. also displayed 23-64 % mycelial growth inhibition of B. fabae under in vitro conditions (Sahile et al, 2009), Ahmed (2015) and El-Banoby et al (2013) have reported the inhibitory activity of B. subtilis on the mycelial growth of B. fabae by 62.6 % and 67.03 % respectively. Similarly, de Senna and Lathrop (2017) showed that Serratia plymuthica inhibited the growth of Botrytis cinerea by 51 % under in vitro study.…”
Section: Introductionmentioning
confidence: 95%
“…The hitherto studies focused on screening of selected isolates such as Bacillus and Pseudomonas spp. antagonistic to B. fabae under laboratory conditions in Ethiopia (Sahile et al, 2009;Alemu, 2016). However, there is a dearth of information on the genetic identification and plant growth-promoting properties of rhizobacteria isolated from the rhizosphere of faba bean.…”
Section: Introductionmentioning
confidence: 99%